Analytical behaviors of concrete-filled circular stainless steel tubular (CFCSST) stub columns under axial loading. (June 2019) - Ding, Fa-xing; Yin, Yi-xiang; Mao, Jian-feng; Wang, Li-ping; Yu, Yu-jie; Luo, Liang; Yu, Zhi-wu
Abstract: The objective of this paper is to investigate the behaviors of concrete-filled circular stainless steel tubular (CFCSST) stub columns under axial loading. A fine finite 3D solid element model was established, and the FE results revealed that the increased ultimate bearing capacity of CFCSST stub columns compared with their carbon steel counterparts was mainly due to that the confinement effect of CFCSST stub columns was stronger than that of carbon steel counterparts and the stress contribution of stainless steel was higher than that of carbon steel. The stress nephogram was simplified reasonably in accordance with the limit state of core concrete and a formula was proposed to estimate the ultimate bearing capacity of CFCSST stub columns using superposition method. Finally, the difference of the experimental and predicted results using the proposed formula and the existing codes were illustrated.